Development of Antimicrobial Edible Film Enriched with Double Emulsion of Cinnamon (Cinnamomum burmannii) Essential Oil - Kam Natania; Jennifer Alvionita; Dela Rosa (Fakultas Teknologi Industri Pertanian, 2022)
The edible film can be used as a carrier of bioactive compounds that contributed to the shelf life or nutritional benefit of food products; however, the addition of bioactive compounds relied greatly on the compatibility of the bioactive compound toward the edible film matrix. Most of the bioactive compounds are nonpolar which incompatible with the polar nature of the edible film. In this research, the nonpolar essential oil of cinnamon, a potent antimicrobial agent, was made into a double emulsion. The double emulsions were made through a two steps emulsification stages, with CaCl2 as the inner water phase and guar gum as the outer water phase. The physicochemical characteristics (stability, viscosity, and droplet size) and the antimicrobial activity of the double emulsion were observed. The double emulsion showed stability up to 7 days of storage at room temperature with high antimicrobial activity; MBC values of 0.86, 1.37, 0.31, and 0.51 mg/mL against E. coli, S. aureus, R. stolonifera, and A. niger, respectively. Different concentrations (5%,10%,15%) of both emulsions were added into edible film suspension. The formation of double emulsion showed a promising result as a means to incorporate nonpolar compounds into basic edible film formulation to increase its functional properties while retaining their physicochemical characteristic. All formulations showed good edible film characteristics, with edible film with 8% essential oil showing a high inhibition zone (15.81 dan 6.92 mm) toward E. Coli and R. stolonifer, 0.0052 mm thickness, the tensile strength of 6.32 MPa, 13% elongation and WVTR of 1.06 g/cm2.h.